Reaction of the hemocoagulation system to tissue hypoxia in patients with chronic obstructive pulmonary disease - Anna A. Bulanova; Artem E. Aksenenko; Anna S. Bobrovnikova; Galina V. Dudko; Dmitriy S. Slizevich; Ekaterina B. Bukreeva; Michail N. Shpisman; Ivan I. Tyutrin (Бюллетень сибирской медицины)
Background. Nowadays little data related to the hemostatic system and fibrinolysis in patients with chronic obstructive pulmonary disease (COPD) are available. This is due to the lack of standardized methods for studying the hemostasis system, as well as to the lack of a single functional test that allows the evaluation of the complete fibrinogenesis cycle in whole blood.Aim. The aim of our study was to develop a functional test capable of analyzing the blood gas composition in the “point-of-care test” method for the evaluation of the hemostatic potential in patients with COPD, based on a standardized test stimulus, which is tissue hypoxia. The current level of clinical and laboratory diagnostics requires personification and research of the hemo-coagulation system in real time (point-of-care test), which allows low-frequency piezotromboelastography(NVTEG) to be performed.Materials and methods. NVTEG was chosen to estimate the state of the hemocoagulation system. Ten patients with COPD and 10 healthy volunteers were examined. Hypoxia was selected as a standardized test stimulus. Hypoxia conditions were caused by smoking one standard cigarette (composition: resin 10 mg/cig., nicotine 0,7 mg/cig., CO 10 mg/cig.). The degree of tissue hypoxia was assessed with the GASTAT-navi blood gas analyzer.Results. The study has shown that in response to the standard test stimulus, which is the tissue hypoxia caused by smoking of a standardized cigarette, two types of haemostatic potential reaction were detected both in patients with COPD and healthy volunteers. The first type of reaction – “hypercoagulation” – is characterized by the formation of chronometric and structural hypercoagulation at all stages of fibrinogenesis and increased coagulation activity by 25–30% compared with the response in healthy individuals. The second type of reaction – “hypocoagulation” – is characterized by the formation of chronometric and structural hypocoagulation, a decrease in coagulation activity by 25–30% compared with the response in healthy individuals.Conclusion. Test stimulus, which acts as tissue hypoxia, causes a uniform spectrum of changes in the blood gas composition and hemocoagulation system in both healthy volunteers and patients with COPD. The possibility of online assessment of all stages of fibrinogenesis makes it possible to stratify patients with COPD by type of reaction, which is certain to have an important diagnostic and prognostic value and in the future will allow a more personified approach for choosing the treatment tactics.